Determination of Optimal Smoothing Constants for Holt - Winter’s Multiplicative Method (Dhaka University Journal of Science, 2019)
There are many trade time series parade having seasonality. This paper ponders on taking the appropriate smoothing constants of seasonal time series data using Holt-Winter’s exponential smoothing method in demand forecasting of toy production in a company. It is a quantitative technique in forecasting. This forecasting method is used three constants that assign weights to current demands and previous forecasts to decide on a new forecast. We have demonstrated the techniques how to choose these constants by presenting a real life example and calculated corresponding forecast value of this technique for the optimal smoothing constants.Dhaka Univ. J. Sci. 67(2): 99-104, 2019 (July)